Diabetes increases mortality after myocardial infarction by oxidizing CaMKII - Luo, Min (American Society for Clinical Investigation, 2013)
Diabetes increases oxidant stress and doubles the risk of dying after myocardial infarction, but the mechanisms underlying increased mortality are unknown. Mice with streptozotocin-induced diabetes developed profound heart rate slowing and doubled mortality compared with controls after myocardial infarction. Oxidized Ca(2+)/calmodulin-dependent protein kinase II (ox-CaMKII) was significantly increased in pacemaker tissues from diabetic patients compared with that in nondiabetic patients after myocardial infarction. Streptozotocin-treated mice had increased pacemaker cell ox-CaMKII and apoptosis, which were further enhanced by myocardial infarction. We developed a knockin mouse model of oxidation-resistant CaMKIIδ (MM-VV), the isoform associated with cardiovascular disease. Streptozotocin-treated MM-VV mice and WT mice infused with MitoTEMPO, a mitochondrial targeted antioxidant, expressed significantly less ox-CaMKII, exhibited increased pacemaker cell survival, maintained normal heart rates, and were resistant to diabetes-attributable mortality after myocardial infarction. Our findings suggest that activation of a mitochondrial/ox-CaMKII pathway contributes to increased sudden death in diabetic patients after myocardial infarction.